OXIDATION OF GLYCEROL BY STREPTOCOCCUS FAECALIS - Claridge, C. A. (1962)
Claridge, C. A. (Merck Sharp & Dohme Research Laboratories, Rahway, N.J.) and David Hendlin. Oxidation of glycerol by Streptococcus faecalis. J. Bacteriol. 84:1181–1186. 1962.—The nature of the factors in yeast autolysate essential for the oxidation of glycerol by Streptococcus faecalis F24 was examined. Two factors appear to be involved in the oxidation of glycerol. One factor was shown to be an inducer of the enzyme system required for glycerol oxidation; the other was shown to be α-lipoic acid. Minute quantities of glucose will “spark” growth of S. faecalis in a medium containing glycerol and acetate as carbon sources, probably by supplying sufficient energy for induction of the glycerol-oxidation system.